PsycEXTRA Dataset 2003
DOI: 10.1037/e387412004-001
|View full text |Cite
|
Sign up to set email alerts
|

Reporting crime to the police, 1992-2000

Abstract: In 2000 about half the violent crimesrape, sexual assault, robbery, and simple and aggravated assaultcommitted against persons age 12 or older were reported to the police, according to the National Crime Victimization Survey (NCVS). About a third of both property crimesburglary, motor vehicle theft, and property theft-and pocket pickings or purse snatchings were also reported. Thirty-nine percent of the 25.4 million crimes estimated from victims' survey responses were reported to law enforcement authorities. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(200 citation statements)
references
References 0 publications
9
174
2
3
Order By: Relevance
“…In the micro-context of police-citizen encounters, citizens' compliance makes the performance of police tasks easier (Mastrofski, Snipes, and Supina 1996;McCluskey 2003;McCluskey, Mastrofski, and Parks 1999), and can be expected to result in less use of force by police and fewer injuries to both police and citizens. Second, citizens who see the police as legitimate might be expected to more readily cooperate with police and other legal actors, for example, in reporting crime, and perhaps in providing information (Hart and Rennison 2003). Third, citizens who regard legal authorities as legitimate may be less likely to break the law.…”
Section: Police Legitimacy and Pro Cedur Al Justicementioning
confidence: 99%
“…In the micro-context of police-citizen encounters, citizens' compliance makes the performance of police tasks easier (Mastrofski, Snipes, and Supina 1996;McCluskey 2003;McCluskey, Mastrofski, and Parks 1999), and can be expected to result in less use of force by police and fewer injuries to both police and citizens. Second, citizens who see the police as legitimate might be expected to more readily cooperate with police and other legal actors, for example, in reporting crime, and perhaps in providing information (Hart and Rennison 2003). Third, citizens who regard legal authorities as legitimate may be less likely to break the law.…”
Section: Police Legitimacy and Pro Cedur Al Justicementioning
confidence: 99%
“…It appears that the Hispanic victims in this study operate on a seriousness dimension and report crime when a certain level of harm or perceived harm is inflicted. One of the most important reasons victims give for not reporting crime to the police is that "it was not serious enough" (Hart & Rennison, 2003;Skogan, 1984). Furthermore, Rennison (2010) found that among Hispanic victims of violence, the least likely scenario to be reported to the police was a single male who sustained no injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The reporting rate by those aged 12 to 15 was 26% as opposed to 55.4% among over-65 s. By analysing data collected between 1992 and 2005, the authors discovered that less than a third of violent incidents against minors were reported to the police and that violence against young blacks was the crime most likely to be reported as opposed to crimes committed against young whites or Asians. There are also numerous stratification factors that affect re- Another important matter is that the position of the police in the criminal justice system can have a direct effect on the number of crimes recorded and how they are classified (Hart & Rennison, 2003). In some countries the police can work with absolute independence, while in others they may work under the close supervision of the public prosecutor or the court.…”
Section: Literature Reviewmentioning
confidence: 99%